“LONTAR PRASI” : THE PRESERVATION OF TENGANAN PAGRINGSINGAN TRADITIONAL VILLAGE - Putra, I Nyoman Agus Suarya; Yusa, I Made Marthana; Willdahlia, Ayu Gede; Adiftia, Mohammad Ryan (Seni Media Rekam ISI Surakarta, 2022)
Prasi art is a cultural heritage that remains in the traditional Balinese Aga (ancient) village of Tenganan Pagringsingan that must be preserved and promoted. One of the measures that may be implemented is the creation of informative and educative audio-visual works. The creation of this work focused on how to produce and draw on lontar prasi typical of Tenganan Pagringsingan traditional village. The creation of the work utilized an expository documentary approach involving pre-production, production, and post-production phases. The results of the work creation show that the video artwork was highly informative and detailed, appropriate to the context discussed, so it deserves to be presented.